Moisture Sorption Isotherms of Whey Powder Spray in the 10–40°C Temperature Range - J. Stencl (Adsorption Science & Technology)
The results of water sorption tests on whey powder spray carried out under laboratory conditions were presented together with mathematical analyses of the sorption isotherms. Moisture equilibrium data were investigated at air temperatures over the temperature range 10–40°C and water activity ranging from 0.3 to 0.99. The experimental procedure used was a gravimetric dynamic method with continuous registration of sample weight changes. A special laboratory drying device was developed for the purpose. The sorption capacity decreased as the temperature increased. Re-hydration of the dried material resulted in hysteresis but this phenomenon was limited. Four models of equilibrium moisture content/water activity (Chung-Pfost, Halsey, Henderson and Oswin) were evaluated for their ability to fit the data for the samples tested. The Henderson equation provided a good model for moisture adsorption and desorption by whey powder spray.